2015
DOI: 10.1667/rr14047.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Impact of Neonatal Exposure to Total Body Gamma Radiation on Secondary Lymphoid Organ Structure and Function

Abstract: The acute period after total body irradiation (TBI) is associated with an increased risk of infection, principally resulting from the loss of hematopoietic stem cells, as well as disruption of mucosal epithelial barriers. Although there is a return to baseline infection control coinciding with the apparent progressive recovery of hematopoietic cell populations, late susceptibility to infection in radiation-sensitive organs such as lung and kidney is known to occur. Indeed, pulmonary infections are particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…These data are further supported by the finding that treatment with IL-22, in mice receiving bone marrow transplantation, resulted in increased intestinal stem cell recovery, in enhanced epithelial cell regeneration, and in reduction of intestinal GvHD ( 36 ). Given the role of ILC3 in lymphoid organogenesis and in lymphoid tissue remodeling, a role for these cells could also be envisaged in the regeneration of lymphoid tissues damaged by radiations ( 38 , 40 ). Of note, ILC3-derived IL-22 can also favor the recovery of thymic epithelial cells, thus allowing a more efficient and rapid reconstitution of T-cell compartment (Table 1 ) ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are further supported by the finding that treatment with IL-22, in mice receiving bone marrow transplantation, resulted in increased intestinal stem cell recovery, in enhanced epithelial cell regeneration, and in reduction of intestinal GvHD ( 36 ). Given the role of ILC3 in lymphoid organogenesis and in lymphoid tissue remodeling, a role for these cells could also be envisaged in the regeneration of lymphoid tissues damaged by radiations ( 38 , 40 ). Of note, ILC3-derived IL-22 can also favor the recovery of thymic epithelial cells, thus allowing a more efficient and rapid reconstitution of T-cell compartment (Table 1 ) ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, it remains to be determined whether ILC3 also contribute to the regeneration of secondary lymphoid organs. In this context, it is recently shown that gamma irradiation used in conditioning regimen before HSCT may exert a long-lasting effect on secondary lymphoid organ structure and function ( 40 ). Also, ILC2 appear to be involved in epithelial tissue repair, particularly in lung tissues; however, no data are available to support an actual protection exerted by these cells in GvHD-induced tissue damages ( 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our group has demonstrated, in both adult and neonate models of lung irradiation, that low-dose irradiation leads to late susceptibility to pulmonary infections (5456). However, further investigations have indicated these altered immune responses are subsequent to effects on different cell populations dependent on the age at the time of irradiation, i.e., loss of epithelial (club) cells (54) in the adult animals versus alterations in secondary lymph organs in the neonates (172), indicating that age and/or development status may also inform mitigation strategies. It is therefore likely that combination approaches will need to be tailored to the most critically affected organs or those most at risk, depending on the affected volume.…”
Section: Discussionmentioning
confidence: 99%
“…These harms can worsen with allo-HSCT following the occurrence of GVHD due to donor T lymphocytes [ 66 ]. An animal experimental model of aGVHD demonstrated that host-originated IL-22 could avoid the onset of GVHD, and that gut ILC3 cells are the principal makers of IL-22 after total body irradiation therapy [ 67 , 68 , 69 ]. Furthermore, ILC3-originated IL-22 can also promote thymic epithelial cell recovery, thus permitting a prompter re-formation of the T cell subset [ 70 ].…”
Section: Acute Leukemiamentioning
confidence: 99%